The Eurasian Tiger: How Deep Are its Claws? - N. Shaik-Peremanov (BRICS Law Journal, 2024)
The Shanghai Corporation Organisation arose from a set of desired ideals in the Eurasian region bolstered primarily by countries such as Russia and China. With diverging cultural, political, religious, and economic values, the security and economic values were primate on the Organisation’s Agenda giving way to the formation of a strong regional alliance that grew from a five Member State Organisation. Within the Organisation, the ideals of human security, regional security, information sharing and economic development with cooperation find common ground. Though challenged differing values, the work traverses the historical, legal, and other journeys to one that has successfully found its way into the international arena with the likes of the United Nations. This paper reviews the work.